2017
DOI: 10.1016/j.scitotenv.2017.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Transport and attenuation of Salmonella enterica, fecal indicator bacteria and a poultry litter marker gene are correlated in soil columns

Abstract: Millions of tons of fecal-contaminated poultry litter are applied to U.S. agricultural fields annually. Precipitation and irrigation facilitate transport of fecal-derived pathogens and fecal indicator bacteria (FIB) to groundwater. The goal of this study was to compare transport of pathogens, FIB, and a microbial source tracking marker gene for poultry litter (LA35) in a simulated soil-to-groundwater system. Nine laboratory soil columns containing four different soil types were used to evaluate microbial trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 47 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…Common Salmonella sp. are faecal indicator bacteria (Mantha et al ., ) and were significantly reduced after C. megacephala‐ treated swine manure (Fig. ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Common Salmonella sp. are faecal indicator bacteria (Mantha et al ., ) and were significantly reduced after C. megacephala‐ treated swine manure (Fig. ).…”
Section: Resultsmentioning
confidence: 97%
“…Salmonella sp. are faecal indicators in wastewater (Mantha et al, 2017), which suggested that C. megacephala composting might reduce the risk in Salmonella Enteritidis, a standout foodborne disease worldwide (Borges et al, 2017). Based on the correlation analysis of Pseudomonas, Prevotella and heavy metal speciation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Contamination with human fecal material from untreated sewage poses the greatest health risk because of the host specificity of many pathogens (Eisenberg et al, 2016), especially viruses. However, contamination from some animal sources, such as livestock and poultry, also poses a health risk due to the presence of pathogenic bacteria, such as Campylobacter, Escherichia coli O157:H7 and Salmonella, as well as the protozoa Giardia and Cryptosporidium (Bradshaw et al, 2016;Ehsan et al, 2015;Haack et al, 2016;Mantha et al, 2017). There is an indeterminate risk associated with non-point source pollution events, such as fecal deposition from some wildlife.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Li et al (2015) reported relatively low sensitivity of the LA35 marker when applied to poultry litter samples, although the authors did not compare with the CL marker or any other poultry‐specific marker. Unfortunately, additional studies using the LA35 poultry marker did not apply the marker to environmental waters, but rather to experimental microcosms to evaluate persistence (Nayak et al, 2015; Mantha et al, 2017). Therefore, this is the first study to evaluate both poultry‐specific markers within a single watershed over a prolonged period of time.…”
Section: Resultsmentioning
confidence: 99%